PENGARUH PENDIDIKAN KESEHATAN P3K BALUT BIDAI PADA CEDERA BELADIRI TERHADAP PENGETAHUAN DAN KETERAMPILAN ANGGOTA TAPAK SUCI - Yuhaning Audiya; Meida Laely Ramdani (MEDIA ILMU KESEHATAN, 2020)
Background: First Aid is a temporary treatment for accident victims before getting more comprehensive help from health workers. In sports, it’s necessary to have knowledge about sports injuries includes the causes, prevention, and skills in handling the injuries. Objective: This research aimed to analyze the effect of the education of first aid using splint and bandage on martial arts injuries toward the knowledge and skills of Tapak Suci members. Methods: This was pre-experimental quantitative research with pre-test post-test design without a control group. There were 50 respondents as the population and 30 respondents were taken as the research sample using a simple random sampling technique. The research data were collected using a questionnaire and observation sheets. Then they were analyzed using the Paired Sample T-test. Results: The results showed the average score of respondents' knowledge before and after the health education was 10.7 and 16.07 respectively. While that of skills before and after the health education was 4.23 and 7.53 respectively. Based on Paired T-test sample results, it was obtained that p-value = 0.001. Conclusion: There is an effect of the education first aid using splint and bandage on martial arts injuries toward the knowledge and skills of Tapak Suci.